2012
DOI: 10.1111/j.1365-2494.2012.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stocking rate and calving date on grass production, utilization and nutritive value of the sward during the grazing season

Abstract: A 2-year whole-farm system study compared the accumulation, utilization and nutritive value of grass in spring-calving grass-based systems differing in stocking rate (SR) and calving date (CD). Six treatments (systems) were compared over two complete grazing seasons. Stocking rates used in the study were low (2Á5 cows ha À1 ), medium (2Á9 cows ha À1 ) and high (3Á3 cows ha À1 ), respectively, and mean CDs were 12 February (early) and 25 February (late). Each system had its own farmlet of eighteen paddocks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 36 publications
(70 reference statements)
13
62
1
Order By: Relevance
“…Early lactation grazing management study can be used to provide grass-based dairy farms with information on how to deal with fluctuations in grass supply during early spring. McCarthy et al (2012) previously reported variability of grass production, particularly during the spring period under Irish climatic conditions. The spring, during which the present experiment was conducted was no different, as grass growth in March was 41% higher and grass growth in April was 22% lower than the previous 10-year average.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Early lactation grazing management study can be used to provide grass-based dairy farms with information on how to deal with fluctuations in grass supply during early spring. McCarthy et al (2012) previously reported variability of grass production, particularly during the spring period under Irish climatic conditions. The spring, during which the present experiment was conducted was no different, as grass growth in March was 41% higher and grass growth in April was 22% lower than the previous 10-year average.…”
Section: Discussionmentioning
confidence: 94%
“…The greatest opportunities to increase the contribution of grazed grass to the dairy cow diet exist in early spring and late autumn; however, spring grass growth can be extremely variable resulting in deficits in grass supply (McCarthy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The provision of an adequate amount of conserved grass silage for the winter feeding period is a key requirement of Irish dairy systems (McCarthy et al, 2013). The current study was executed from late spring to autumn, as it is during this Means within a row with different superscripts differ (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrate supplementation was only used when a feed deficit occurred, because of a reduction in pasture growth for all treatments and at a similar rate per cow on those occasions. When feed deficits arose, for individual treatments, conserved forage produced within that treatment was used to supplement feed supply (McCarthy et al, 2013 Pasture measurements HM (>4 cm) was calculated by cutting four strips (1.2 m × 10 m) with a motor Agria (Etesia UK Ltd, Warwick, UK) from each treatment area, three times per week. Ten grass height measurements were recorded before and after harvesting on each cut strip using a plate meter with a steel plate (diameter 355 mm and 3.2 kg/m 2 ; Jenquip, Fielding, New Zealand).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental site was used to compare diverse animal genotypes and nutritional treatments during the 10 year evaluation period (Coleman et al, 2008;Horan et al, 2004;McCarthy et al, 2012). In all experiments, a rotational grazing management system was practiced usually commencing in early February and concluding in late November each year.…”
Section: Agronomymentioning
confidence: 99%